Fast and low cost method for identification of bacterial colonization in burn wounds (2018)
This report provides an analysis and evaluation of the existing needs in a hospital environment, specifically in the area of skin burns. The mentioned needs were met through an observation process carried out at Simón Bolívar Hospital, Santafe Foundation, University of the Andes and through interviews with people who have suffered this type of injury. The evidence of the observation carried out shows that between 53 and 93 of every 1000 people presented an infected wound after 2 or 3 days of suffering the injury. In addition, the report finds that the processes of detection of infections that are carried out now take a long time, which does not allow timely and accurate treatment, which is one of the main problems in the Burned Pavilions. Taking into account the above, a method of rapid identification of bacterial colonization was designed in patients with second and third degree burns in clinical settings, which consists of a gold interdigitated biosensor that translates the concentration of bacteria in a sample into electrical signals from impedance and capacitance. This response variable allows classifying the device as a rapid screening test, easy to use, stable, efficient and low cost.